A Zariski topology for semimodules - (:unkn) unknown (My University, 2011)
0

Given a very strong multiplication semimidule M over a commutative semiring R, a Zariski topology is defined on the spectrum $Spec _k$(M) of prime k-subsemimodules of M. The properties and possible structures of this topology are studied. 2000 Mathematics Subject Classifications: 16Y60
Keywords: Matematik